Relationship of coronary heart disease and comorbide dental background - V. A. Khaptanova; A. D. Golmenko; A. Yu. Khaptanov; D. Yu. Gamayunov (Acta Biomedica Scientifica, 2021)
Cardiovascular disease has serious economic and social consequences that affect people, health systems and societies around the world. Ischemic heart disease is one of the main global causes of death of the population, and its growth is predicted in the coming years. This fact continues to be of serious concern to health, social and economic services. Cardiovascular disease remains the most common cause of death, and age-standardized rates are higher for men than for women. Cardiovascular comorbidity increases significantly with age.The combination of ischemic heart disease and comorbid pathology is noted in cancer incidence, bronchial asthma, non-alcoholic fatty liver disease, type 2 diabetes mellitus, chronic obstructive pulmonary disease, periodontal disease, etc. It is necessary to analyze the existing disease with past diseases, risk factors and predictors available in the patient. The presence of concomitant diseases quite often requires additional diagnostic methods and changes in the tactics of treating coronary heart disease due to the fact that some of them are a contraindication to the use of certain groups of drugs. Periodontal disease includes a wide range of inflammatory conditions that affect the supporting structures of the teeth, which can lead to tooth loss and contribute to systemic inflammation. Periodontal disease is associated with several systemic diseases, one of which is coronary artery disease. It is imperative that clinicians understand the link between periodontal disease and cardiovascular disease. Comprehensive treatment of periodontitis and restoration of a healthy periodontium can help reduce overall inflammation in the body and reduce the risks of coronary heart disease.